Prioritas Wilayah Pengembangan Ternak Ruminansia di Kabupaten Tasikmalaya The Priority Region of Ruminant Development in Tasikmalaya District - Darsono, W.; Putri, E. I. K.; Nahrowi, Nahrowi (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2016)
The objectives of researches were to determine the priority of ruminant development region in Tasikmalaya District. The Base Area anayisis was used in this research through the Location Quotion (LQ), The potential analysis of feedstuff carrying capacity werw also observed. Ruminants population in Tasikmalaya District were 127,847. 89 Animal Unit (AU) consist of beef cattle 50,137 AU, dairy cattle 2,106.00 AU, buffaloes 13,568.85 AU, goats 47,55.80 AU and sheep 14.482,24 AU. There were 6 subdistrictss (Cipatujah, Karangnunggal, Cikalong, Pancatengah, Cikatomas) as base area of beef cattle, 1 subdistrict (Pagerageung) as base area of dairy cattle, 4 subdistricts (Cipatujah, Karangnunggal, Culamega, Leuwisari) as base area of buffaloes, 3 subdistricts (Leuwisari, Sariwangi, Padakembang) as base area of goats, and no base area for sheep. Potential production of feedstuff was 801,202.62 Dry Matter tons/year spread in every subdistrict, especially in the base area of ruminants. Tasikmalaya District has the carryng capacity 341,174.08 AU of ruminant and still be able to increase up to 213,326.19 AU or 160% of the real population. The best priority region of ruminant development in Tasikmalaya district was in Cipatujah in the base area and Bojonggambir for non base area.